2019
DOI: 10.1016/j.tree.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A Horizon Scan of Emerging Issues for Global Conservation in 2019

Abstract: We present the results of our tenth annual horizon scan. We identified 15 emerging priority topics that may have major positive or negative effects on the future conservation of global biodiversity, but which at present, have low awareness within the conservation community. We thus hope to focus increased research and policy attention on these areas, improving the capacity of the community to mitigate impacts of issues likely to have negative effects, and maximise the benefits of issues that provide opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 53 publications
0
43
0
1
Order By: Relevance
“…Although these GE crops are not yet produced commercially, a novel terrestrial source of EPA and DHA, produced on an industrial scale, would make these bioactive fatty acids broadly available to terrestrial herbivorous insects in regions where these crops are grown (Colombo et al ., ; MacDonald et al ., ). The novel introduction of these bioactive compounds to terrestrial crops could impact trophic ecology and, as such, this has been considered as a top emerging issue of ecological concern (Sutherland et al ., ). The development of these technological advancements has piqued an interest in understanding the roles of dietary EPA and DHA in the physiology, behaviour and ecology of terrestrial insects.…”
Section: Introductionmentioning
confidence: 97%
“…Although these GE crops are not yet produced commercially, a novel terrestrial source of EPA and DHA, produced on an industrial scale, would make these bioactive fatty acids broadly available to terrestrial herbivorous insects in regions where these crops are grown (Colombo et al ., ; MacDonald et al ., ). The novel introduction of these bioactive compounds to terrestrial crops could impact trophic ecology and, as such, this has been considered as a top emerging issue of ecological concern (Sutherland et al ., ). The development of these technological advancements has piqued an interest in understanding the roles of dietary EPA and DHA in the physiology, behaviour and ecology of terrestrial insects.…”
Section: Introductionmentioning
confidence: 97%
“…Soil microorganisms play critical roles in the flow of energy and materials in ecosystems (Martina et al, 2012). In particular, rhizosphere microorganisms are essential for plant growth, alleviate pathogen colonization, and maintain rhizosphere microecological balance (Li et al, 2014;Zhou et al, 2014), and it is increasingly recognized that harnessing rhizospheric microbiomes offers new opportunities to influence plant performance through adequate management (Sutherland et al 2019). The present pilot study used high-throughput sequencing of community phylogenetic marker genes to evaluate the microbial diversity in Ulmus pumila L. var.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the current study was to explore the response of soil microbial community diversity to seasonal changes. It addresses Further, the study aimed to address the lack of knowledge about elm rhizospheric microbial communities, which could provide useful information for the protection and utilization of sparse elm forests as harnessing rhizospheric microbiomes is increasingly recognized as a possible lever to influence plant performance through adequate management (Sutherland et al, 2019). The study also may be helpful to provide an important theoretical basis for understanding the ecological and environmental construction of the OSL hinterland.…”
Section: Introductionmentioning
confidence: 99%
“…We adapted the Delphi-like method used in other horizon scans (Mukherjee et al, 2015;Sutherland et al, 2018). Through anonymity, iteration, facilitated discussion, structured elicitation, and aggregation of individual judgments, the method is designed to democratically incorporate a range of perspectives and mitigate psychological biases that typically befall individuals and groups (Burgman, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, other horizon scans have set a precedent of informing policy and decisions. For example, priorities identified in an Antarctic Science Horizon Scan (Kennicutt et al, 2014) were used to invoke financial support for joint science programs on ice sheet research (National Science Foundation, 2016), and issues identified in annual global conservation scans (e.g., Sutherland et al, 2018) have informed the U.K.'s Natural Environment Research Council's "Forward Look" strategic planning.…”
Section: Introductionmentioning
confidence: 99%